ASSESSMENT AND EVALUATION METHODS AS TOOLS FOR MEASURING STUDENTS’ KNOWLEDGE, SKILLS AND CRITICAL THINKING ABILITIES - BEHRUZ SALOHIDDINOV VAHOBIDDIN O‘G‘LI, (Ta'lim innovatsiyasi va integratsiyasi, 2026)
ABSTRACT   Assessment and evaluation are essential components of the educational process, serving as instruments to measure students’ academic achievement, skill development, and critical thinking capabilities. Effective assessment methods provide educators with valuable  insights  into  learners’  strengths,  weaknesses,  and  areas  requiring improvement,  thereby  guiding  instructional  strategies  and  curriculum  design.  This study  explores  various  assessment  techniques,  including  formative  and  summative evaluations, standardized testing, performance-based assessments, and self-assessment approaches,  emphasizing  their  role  in  fostering  analytical  thinking  and  problem-solving skills.